12 years of archaeological research on hydraulic works at the Rosa María site - Arce Cerdas, Marco (2025)
Introduction: A longitudinal investigation has been implemented in the Rosa María archaeological monument (in Pacayitas, Turrialba, Costa Rica) where interdisciplinary has been essential to get closer to understanding, above all, the ancient hydraulic works that are part of this pre-Columbian settlement.Objective: Through this work, a review and synthesis is made –of these 12 years of research – through the different investigative stages carried out there; as well as its scope and main results obtained are addressed.Method: A series of basic/traditional techniques in archeology were combined, such as: surveys, maps, vertical and horizontal excavations, analysis of the different recovered materials; as well as some specialized ones coming from other fields such as photogrammetry, topography, as well as tools linked to the management and diffusion of cultural heritage.Results: It was possible to know the structural/constructive nature of the architecture related to the ancient management of the vital liquid (water boxes, catchment boxes, filter galleries, channels, etc.), as well as to identify certain petroglyphs associated with them; all this to understand more about the hydraulic systems of pre-Columbian Costa Rica.  [Continue reading in the article]